Evaluation of household expenditure in the united states: pre-covid and post-covid statistical analysis - Mobasshira Zaman (International Journal of Research in Industrial Engineering)
The COVID-19 pandemic has caused unprecedented disruption to the global economic structure, resulting in significant changes in spending patterns for households worldwide. Developed countries like the United States have been affected as well, struggling to return to pre-pandemic stable economic situations. This study focuses on the impact of the pandemic on household expenditure in the United States, using ANOVA to compare household expenses between the pre-COVID period in 2018 and the post-COVID period in 2021. The results of the study showed a significant increase in all types of household expenditure from pre-COVID to post-COVID periods, highlighting the correlation between the pandemic and changes in spending habits. This trend is further fueled by price increases in daily necessities, inflation of the dollar, and scarcity of goods. The analysis also revealed that the trend was increasing, emphasizing the need for immediate policy interventions to address the issue. Further research is needed to identify the specific types of expenditure driving this increase and the underlying reasons behind it. The implications of the study are significant for policymakers and economists as they underscore the need for effective interventions to stabilize household expenditure and promote economic recovery in the wake of the pandemic. The findings also highlight the importance of utilizing statistical methods such as ANOVA to evaluate complex economic systems and guide evidence-based policy interventions. As future research continues to explore the impact of the pandemic on economic structures worldwide, this study provides valuable insights into the specific changes in household expenditure in the United States, emphasizing the urgent need for targeted policy interventions to address these changes.